English Grammar Understanding with Ms Noning on TikTok - Ida Fitri Anggarini; Melvina Murdliyana; Nala Nurissaadah; Pratiwi Nur Imansari; Afifatul Khoiriyah; Aisya Lailatul Masruroh (ELITE Association Indonesia, 2023)
ABSTRACTEnglish grammar is an interesting object to be discussed by all learners specifically for English as Foreign Language (EFL) learners in the digital age. It is because there are efforts to understand the correct grammar in each sentence by utilizing the gadget. Thus, this study aimed to find out Ms. Noning’s grammar explanation of several artists in Indonesia through her TikTok account (English with Ms. Noning). The data are taken from the TikTok videos on Ms. Noning’s TikTok account over the last six months of her grammar explanation and review (from December 2022 to February 2023) which focused on her grammar explanation of several artists in Indonesia. The study revealed that ten Indonesian artists have reviewed her with several tenses or grammar from present to future. Analyzing the videos and comments shows a good connection between Ms. Noning and the viewer (digital learner). This study is good and beneficial to enrich grammar understanding by utilizing technology. Further, this is one of the good ways to learn grammar easier in this digital age Keywords: English grammar; TikTok; Digital age